Janus Micromotors: Hydrogel‐Based Janus Micromotors Capped with Functional Nanoparticles for Environmental Applications (Adv. Mater. Technol. 8/2020). Issue 8 (10th August 2020) - Lin, Xinyi; Zhu, Hong; Zhao, Zhe; You, Chunyu; Kong, Ye; Zhao, Yuting; Liu, Jinrun; Chen, Hong; Shi, Xiaojie; Makarov, Denys; Mei, Yongfeng
Abstract : In article number 2000279, Denys Makarov, Yongfeng Mei and co‐workers report a cost‐effective fabrication method of Janus micromotors by capping hydrogel microspheres with functional nanoparticles. The image demonstrates a potential environmental application of the multifunctional Janus particles – they are guided relying on the interaction with an external magnetic field and perform useful tasks on water cleaning from pollutants (represented by blue colored spheres).